Peran Sarjana Perempuan dalam Perspektif Hukum Islam (Al-Qur’an dan Hadis) - Laily Liddini; Ade Arifin; Novita Nur Anggraini; Faros Iqbal; Nila Ni’matul Maula (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This article examines the role of female scholars in the Perspective of the Qur'an and Hadith. Women are part of Islam and have a big contribution in Islam. The image of women as sidekicks wingking doesn't give a role in the public sphere, so their existence is not taken into account. Islam strongly recommends higher education for women, and having a very important social role equal to men, this is evidenced by the existence of several female figures in the public sphere such as in the fields of politics, economics, health and others. The purpose of this paper is to find out the role of female scholars in the view of Islamic law. This study uses the library research method with qualitative descriptive analysis by collecting materials related to literary sources derived from books, commentaries, hadith books, journals, articles and writings related to the role of female scholar. The results of this study indicate that the more female graduates will open up opportunities for the welfare of social life in society. The use of a female scholar in educating the nation's generation will increase the nation's education level. So that civilized justice can be created and there is no more discrimination against women. Women can actualize themselves in various fields according to their talents and interests, without eliminating their duties and responsibilities within their families.